Primary congenital glaucoma - Monika Nowak; Maciej Dyda; Julia Górczyńska; Katarzyna Mazur; Kinga Zimna; Michał Gebuza (Termedia Publishing House, 2024)
Primary congenital glaucoma (PCG) is a developmental disorder affecting the trabecular meshwork and anterior chamber angle, leading to increased intraocular pressure (IOP) and potential vision loss. The early symptoms of PCG are already apparent during the first medical visits. Early diagnosis is crucial to be able to implement appropriate treatment to prevent the disease from developing as soon as possible. Its onset occurs before age three, with nonspecific symptoms such as eye rubbing, photophobia, and blepharospasm. Despite rare occurrence and heterogeneous prevalence depending on the geographical region, PCG accounts for a significant proportion of childhood blindness. The etiology of PCG involves genetic factors; the kinship of parents may increase its prevalence. Nonspecific symptoms of PCG necessitate vigilant examination to enable early detection. Diagnostic criteria include elevated IOP, optic nerve damage, corneal changes, and visual field defects. Treatment mainly relies on goniotomy and trabeculectomy in combination with pharmacotherapy.